Effect of spermatic nuclear quality on live birth rates in intracytoplasmic sperm injection - Maroua Hachemi; Mustapha Bensaada; Abdelkader Rouabah; Abdelali Zoghmar; Sebti Benbouhedja; Leila Rouabah; Mehdi Benchaib (Wolters Kluwer Medknow Publications, 2019)
Background: Our study defines the clinical role of sperm DNA damage in the assisted reproductive technology procedure. Aim: To investigate if the compaction of chromatin explored added to the analysis of the sperm DNA fragmentation allows obtaining a new indicator for sperm genome quality linked to live birth rate (LBR). Design: This was a prospective study, undergoing 101 cycles in the intracytoplasmic sperm injection (ICSI) program. Materials and Methods: The sperm DNA fragmentation index (DFI) has been measured with sperm chromatin dispersion examination. The sperm decondensation index (SDI) of chromatin has been measured with aniline blue procedure; with these indexes, a new parameter has been created: DFI × SDI. Statistical Analysis: Pearson's correlation coefficient, Student's t-test, and Chi-square test were used. The quantitative variables were described as mean ± standard deviation. Multivariate logistic regressions were performed with live birth as outcome. Results: The sperm concentration, motility, and normal morphology were lower when the DFI was high (P = 0.001). The fertilization rates and the number of obtained embryos were not statistically significant different according to the DFI groups. The SDI does not appear to be linked either with the spermatic parameters or with the ICSI parameters. A low DFI seems to be a beneficial factor to obtain a live birth in ICSI procedure (P = 0.064). In case of high DFI, a high SDI allows to obtain a higher LBR than a low SDI. Conclusion: The DFI is a good prognostic for a delivery rate in ICSI procedure, and the SDI could be added to DFI to create a new parameter of sperm nuclear quality. This new parameter seems to be linked to LBR.